APLIKASI METODE FOAM-MAT DRYING DALAM PEMBUATAN BUBUK SUSU KEDELAI INSTAN - Dian Purbasari (JURNAL AGROTEKNOLOGI, 2019)
As one of the products from soybean, soybean milk is widely known and appreciated by the public because of its benefits for health. Problems are often encountered in the processing of liquid soybean milk, such as short shelf life of it and easy to loss of quality. One alternative treatment that can extend the shelf life is to turn it into an instant soybean milk powder by drying method. Making instant soybean milk powder in this study used a foam-mat drying method. The purpose of this research was to study the application of foam-mat drying method on the characteristic (quality) of instan soybean milk powder produced. The results showed that the best treatment according to the drying time parameters was at 10% dextrin and 1% Tween 80. Physical characteristics of instant soybean milk powder had the highest yield values (16.10%) at a drying temperature of 60°C, the value of lightness (L) about 84.2; value of redness (a) about 1.3; yellowish value (b) about 24,and water absorption (DSA) of 1.68 mL/g. Chemical analysis resulted that water content of 3.05% at the drying temperature of 70°C, while the highest protein content at the drying temperature of 60°C amounted to 17.34% and the highest fat content about 11.36% at drying temperature of 50°C. Keywords: foam-mat drying, instant, shelf life, soybean milk